2019
DOI: 10.3390/ijms20174094
|View full text |Cite
|
Sign up to set email alerts
|

Mice Exposed to Combined Chronic Low-Dose Irradiation and Modeled Microgravity Develop Long-Term Neurological Sequelae

Abstract: Spaceflight poses many challenges for humans. Ground-based analogs typically focus on single parameters of spaceflight and their associated acute effects. This study assesses the long-term transcriptional effects following single and combination spaceflight analog conditions using the mouse model: simulated microgravity via hindlimb unloading (HLU) and/or low-dose γ-ray irradiation (LDR) for 21 days, followed by 4 months of readaptation. Changes in gene expression and epigenetic modifications in brain samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…1 A–C), indicating distinct transcriptomic profiles are generated following each condition. Similar outcomes were also observed in our previous report that analyzed brain tissues at 4-months post-exposure 18 , indicating LDR, HLU, and simSpace independently trigger divergent pathways post-exposure. Interestingly, post-HLU appears to produce a large number of transcriptional changes compared to post-LDR alone, indicating altered gravity may cause pronounced physiological impairments.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…1 A–C), indicating distinct transcriptomic profiles are generated following each condition. Similar outcomes were also observed in our previous report that analyzed brain tissues at 4-months post-exposure 18 , indicating LDR, HLU, and simSpace independently trigger divergent pathways post-exposure. Interestingly, post-HLU appears to produce a large number of transcriptional changes compared to post-LDR alone, indicating altered gravity may cause pronounced physiological impairments.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, spleens and blood of mice were analyzed by RNAseq and hematological analyses, respectively, at 7-days post-simSpace. Previous studies in our lab have developed a simSpace model of low-dose radiation (LDR, 0.04 Gy) and hindlimb unloading (HLU) that mimics astronauts in-orbit on the International Space Station (ISS) 18 . Analyses at 7-days post-simSpace provide insight into the immediate early responses similarly experienced by crew during Earth readaptation, a critical time point of equalizing homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the space environment is fundamentally different from Earth. Microgravity and ionizing radiation compose a unique set of physiological stressors, the effects of which remain to be fully characterized 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation produced many different neurophysiological alterations, which have been well-measured in the perirhinal cortex, including changes in both intrinsic and extrinsic neuronal properties [69]. Studies in rodents also showed that the effects of irradiation on CNS transcriptional activity and epigenetic state can be potentiated by simulated microgravity [70].…”
Section: Model Organism Genetic Background Radiation Source Effectmentioning
confidence: 97%